Application of a cognitive model of emotional appraisal to the board evaluation function of a program that plays chess - Laureano-Cruces, Ana Lilia (2012)
This paper describes the analysis and design of a cognitive emotional assesment model. This model is based on the goals looked for a chess player during a game. The model affects the output of the board evaluation function of a computational agent which plays chess, giving more weight to aspects related to the most urgent goals, according to the context. Thus, it perceives environment changes, and consequently changes its choice of the next play. The aim is that the computational agent incorporates into the decision making process, the emotional state and choose the plays based on that state. For that purpose were used tools of cognitive psychology and soft computing in order to simulate emotion, and affect the agent’s behavior computer.